2022
DOI: 10.3389/fpls.2022.998803
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of heading date, culm length, and biomass from canopy-height-related parameters derived from time-series UAV observations of rice

Abstract: Unmanned aerial vehicles (UAVs) are powerful tools for monitoring crops for high-throughput phenotyping. Time-series aerial photography of fields can record the whole process of crop growth. Canopy height (CH), which is vertical plant growth, has been used as an indicator for the evaluation of lodging tolerance and the prediction of biomass and yield. However, there have been few attempts to use UAV-derived time-series CH data for field testing of crop lines. Here we provide a novel framework for trait predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Therefore, RGB image analysis can serve as a valuable tool for crop monitoring [25]. Several studies report that RGB cameras can successfully be used for assessing crop height [26,27], texture [28], crop biomass [29,30], leaf area index (LAI) [31], yield [30,32], lodging [27,28], and to obtain other parameters related to the active photosynthetic canopy and senescence such as green area (GA), greener green area (GGA), and the crop senescence index (CSI) [33]. However, RGB cameras can only provide information in the visual spectral bands, which are limited compared to multispectral or hyperspectral cameras [6].…”
Section: Rgb Cameramentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, RGB image analysis can serve as a valuable tool for crop monitoring [25]. Several studies report that RGB cameras can successfully be used for assessing crop height [26,27], texture [28], crop biomass [29,30], leaf area index (LAI) [31], yield [30,32], lodging [27,28], and to obtain other parameters related to the active photosynthetic canopy and senescence such as green area (GA), greener green area (GGA), and the crop senescence index (CSI) [33]. However, RGB cameras can only provide information in the visual spectral bands, which are limited compared to multispectral or hyperspectral cameras [6].…”
Section: Rgb Cameramentioning
confidence: 99%
“…The results showed that biomass measurements have a strong correlation with UAV-estimated corn height (R 2 = 0.83-0.92). Along these lines, another study predicted biomass from canopy height data in rice [30]. Parameters related to canopy height were calculated with a non-linear time series model.…”
Section: Biomass and Yieldmentioning
confidence: 99%